THE RELATIONSHIP BETWEEN NEEDS FOR DOMINANCE WITH INTENSITY ORGANIZING STUDENT IN FACULTY DA’WAH INSTITUTION (LDF) ALMUDARRIS FKIP AT SYIAH KUALA UNIVERSITY - Wahyuni Wahyuni; Dahliana Abdullah; Abu Bakar (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2016)
The study entitled